Optimal Sensor Placement for Stay Cable Damage Identification of Cable-Stayed Bridge under Uncertainty - Li-Qun Hou; Xue-Feng Zhao; Rui-Cong Han (International Journal of Distributed Sensor Networks)
Large cable-stayed bridges utilize hundreds of stay cables. Thus, placing a sensor on every stay cable of bridges for stay cable damage identification (SCDI) is costly and, in most cases, not necessary. Optimal sensor placement is a significant and critical issue for SCDI. This paper proposes the criteria for sensor quantity and location optimization for SCDI on the basis of the concept of damage identification reliability index ( DIRI ) under uncertainty. Random elimination (RE) algorithm and heuristic random elimination (HRE) algorithm are proposed to solve the sensor quantity optimization calculation problem. Multistage global optimization (MGO) algorithm is also proposed to solve the sensor location optimization calculation problem. A case study is conducted to evaluate and verify the criteria and algorithms. Results indicate that the HRE algorithm can provide better solution with less elapsed time than the RE algorithm can in some cases, and the MGO algorithm can meet the multistage criterion for sensor location optimization and give a satisfying optimized solution. Theoretical analysis and case study results confirm that the criteria are reasonable and suitable for optimal sensor placement for SCDI. The proposed algorithms are effective and efficient for practical optimization calculation.